Electrochemical surface oxidation enhanced Raman scattering. (20th August 2018) - Perales-Rondon, Juan V.; Hernandez, Sheila; Martin-Yerga, Daniel; Fanjul-Bolado, Pablo; Heras, Aranzazu; Colina, Alvaro
Abstract: In this work, an unexpected enhancement of the Raman signal for uric acid during the electrochemical oxidation of a silver electrode is presented. This behavior cannot be easily explained using classical models of Surface Enhanced Raman Scattering (SERS). Time resolved Raman spectroelectrochemistry is used to study this interesting process strongly dependent on the experimental conditions. The new phenomenon was observed in different molecules and was found to be reproducible and robust, allowing us to use this methodology for the determination of citric acid. The enhancement of the Raman signal only takes place when a potential is applied to the electrode and therefore, this new phenomenon can be denoted as Electrochemical Surface Oxidation Enhanced Raman Scattering (EC-SOERS). In this work, EC-SOERS is presented not only as an alternative to SERS for detection of molecules but also as a reproducible process that can be used for quantitative analysis. Graphical abstract: Image 1